Behaviors, hygiene habits, and sources of care among removable complete and partial dentures wearers: A multicenter cross‐sectional study - Radwan Algabri; Ahmed Yaseen Alqutaibi; Sadeq Altayyar; Abdulkarem Mohammed; Ghadeer Khoshafa; Emad Alryashi; Shaher Al‐Shaher; Baghdad Hassan; Gubran Hassan; Motaher Dammag; Sami Al‐Aqab; Shaima Al‐Shami; et al. (Wiley, 2024)
Abstract Objectives There is a lack of data regarding the hygiene practices and sources of care among individuals in Yemen who wear removable complete and partial dentures. The purpose of this study was to explore the behaviors, hygiene habits, and sources of care information among patients who utilize complete and partial dentures in Yemen. Materials and Methods A descriptive cross‐sectional research design was utilized, and a sample of 217 consecutive participants who wore removable complete and/or partial dentures were enlisted. A questionnaire was employed to collect data on demographic information, educational attainment, denture habits, denture cleaning practices, and encountered difficulties. Statistical analysis was conducted using SPSS software, and significance was determined using chi‐square tests, with a significance level of .05. Results The data analysis revealed that a majority of the participants were male (72.4%) and had an average age of 65.14 years. Fifty‐three percent of the participants wore partial dentures, while 34.6% wore complete dentures. Only 6.5% of the participants wore both complete and partial dentures, and 6% wore overdentures. The majority of participants (88.47%) had dentures made of acrylic material. Additionally, 43% of participants wore dentures while sleeping, and 61.3% stored their dentures in dry places without a water‐filled container when not in use. The most commonly reported cleaning methods were water only (24.4%), followed by water and soap (19.4%). Furthermore, a large portion of the participants (59.4%) received denture care information from dentists. However, the majority (59%) did not visit a dentist for regular denture maintenance or any denture‐related issues. The data analysis did not reveal any significant association between age or education level and denture cleaning methods. Conclusion This cross‐sectional survey provides insight into the hygiene knowledge and practices of removable denture wearers in Yemen. The findings underscore the necessity for enhanced oral hygiene education and awareness within this population. The study offers valuable insights for oral health professionals to design targeted interventions and educational initiatives aimed at promoting proper denture care and maintenance. These efforts have the potential to enhance the oral health and overall well‐being of removable denture wearers.